Respuesta :

Recall that

[tex]\tan(x+y)=\dfrac{\tan x+\tan y}{1-\tan x\tan y}[/tex]

and that [tex]\tan\frac\pi4=1[/tex]. So we have

[tex]\tan x+\tan\left(x+\dfrac\pi4\right)=1[/tex]

[tex]\implies\tan x+\dfrac{\tan x+\tan\frac\pi4}{1-\tan x\tan\frac\pi4}=1[/tex]

[tex]\implies\tan x+\dfrac{\tan x+1}{1-\tan x}=1[/tex]

[tex]\implies\dfrac{\tan x(1-\tan x)+\tan x+1}{1-\tan x}=1[/tex]

[tex]\implies\dfrac{1+2\tan x-\tan^2x}{1-\tan x}=1[/tex]

As long as [tex]\tan x\neq1[/tex], we can write

[tex]\implies1+2\tan x-\tan^2x=1-\tan x[/tex]

[tex]\implies3\tan x-\tan^2x=0[/tex]

[tex]\implies\tan x(3-\tan x)=0[/tex]

[tex]\implies\tan x=0\text{ or }\tan x=3[/tex]

[tex]\implies\boxed{x=n\pi\text{ or }x=\tan^{-1}3+n\pi}[/tex]

where [tex]n[/tex] is any integer.

ACCESS MORE